NON-CARCINOGENIC RISK FOR HEALTH OF THE POPULATION DUE TO AIR POLLUTION BY COAL MINE EMISSIONS - Голиков, Роман Анатольевич; Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Корсакова, Татьяна Георгиевна (Medicine in Kuzbass, 2018)
Subject – atmospheric emissions of a coal mine in Novokuznetsk.Objective – to assess the non-carcinogenic risk of the exposure to the emissions into the air basin of «Polosukhinskaya Mine», OJSC, for the population of Novokuznetsk and Novokuznetsk district.Methods. The analysis of the mine’s atmospheric emissions has been carried out on the basis of a study on the volume of maximum permissible emissions (MPE). The indexes of non-carcinogenic hazard of the emissions by the contaminating impurities and pollution sources were determined. The maximum and average annual concentrations of toxic substances from each source of the emissions at each point of the exposure to concentrations (PEC) of toxic substances related to the microdistricts of residential area were calculated based on the data on the distance between each PEC and each source of the emissions, and non-carcinogenic risks to population health were calculated.Main results. Hazard indexes of air emissions by the coal industry enterprise in Novokuznetsk and Novokuznetsk district have been established. The risks of chronic intoxication related to the emissions of such substances as diiron trioxide, sulfur dioxide, carbon oxide, manganese, nitrogen dioxide, coal ash (with a SiO2 content of 20-70 %), fluoride gaseous compounds were calculated. A comparison of total risks with the acceptable levels for each point of the exposure was carried out.Conclusions. «Polosukhinskaya Mine», OJSC, contributes to the pollution of the atmospheric air in Novokuznetsk and Novokuznetsk district, herewith chronic inhalation effect on the health of the population in Novokuznetsk and Novokuznetsk district is not provided.
Keywords: coal mine; atmospheric emissions; contaminating impurities; hazard index; non-carcinogenic risk